Type-2 Fuzzy Logic and Systems Dedicated to Professor Jerry Mendel for his Pioneering Contribution - John, Robert; Hagras, Hani; Castillo, Oscar (Studies in Fuzziness and Soft Computing, 2018)
This book explores recent perspectives on type-2 fuzzy sets. Written as a tribute to Professor Jerry Mendel for his pioneering works on type-2 fuzzy sets and systems, it covers a wide range of topics, including applications to the Go game, machine learning and pattern recognition, as well as type-2 fuzzy control and intelligent systems. The book is intended as a reference guide for the type-2 fuzzy logic community, yet it aims also at other communities dealing with similar methods and applications. .